Evaluation on Effective Dimensions of Base Isolators Applied at Existing RC Building due to Earthquakes - Suranto, Jaka; Aswin, Muhammad; Nursyamsi, Nursyamsi (Syntax Corporation, 2024)
This study investigates the structural performance of High Damper Rubber Bearings (HDRB) as base isolators in reinforced concrete (RC) buildings subjected to seismic loads. Given the potential for damage or collapse in RC buildings during earthquakes, the utilization of base isolators offers a promising solution to mitigate seismic risks. Finite element analysis was employed to assess the displacement efficiency of different HDRB configurations, focusing on the SMP 5 Muhammadiyah building in Surabaya as a case study. Results indicate that HDRB type HH090X6R exhibits superior performance, achieving displacement efficiencies of 90.56% in the x-direction and 95.87% in the y-direction. These findings underscore the importance of selecting optimal base isolator configurations to enhance the seismic resilience of RC structures. The study's implications extend to seismic retrofitting and structural design practices, offering valuable insights for improving the seismic performance of existing buildings and bolstering community resilience to earthquakes.